MRI diagnosis of a juvenile leukoencephalopathy with vanishing white matter: A rare case report from Morocco and literature review - Chaymae Ziani, MD; Hamid Ziani, MD; Khaoula Oukrid, MD; Siham Nasri, MD; Imane Kamaoui, MD; Imane Skiker, MD (Radiology Case Reports)
Leukoencephalopathy with vanishing white matter is a new autosomal recessive inherited disorder disease entity. It is a chronic disease with a progressive course and episodes of exacerbation, the prevalence of which is still unknown. This disease usually occurs in children and is rare, particularly in the non-Caucasian population. Its main symptoms are ataxia and spasticity and MRI is a key diagnostic tool. We present a juvenile-onset Moroccan case of leukoencephalopathy with vanishing white matter. MRI findings in this case included linear high signal intensity on T2-weighted and fluid-attenuated inversion recovery images in the pons, in addition to typical abnormalities in the cerebral white matter. The diagnosis of leukoencephalopathy with vanishing white matter was based on clinical criteria and the typical appearance on a cerebral MRI.